A Comparison of the Application to Architecture of the Ecological and Gestalt Approaches to Visual Perception - (:unkn) unknown (My University, 1984)
This research is a comparison of two psychological theories of visual perception, Gestalt Theory and an Ecological Theory developed by J. J. Gibson, with two theories of architectural composition, theories developed by the Ecole des Beaux-Arts and theories of the Modern Movement in architecture. The objective of the research is to clarify the relation between the psychology of perception and building composition, and thereby to affect how architects are educated and practice.